The Structure and Properties of Sepiolite with Partial Lattice Ions Substituted by Aluminum Ions - Chen, Huiwen; Geng, Junming; Zhang, Zepeng; Jiang, Rui; Zhai, Jingya; Zhang, Jinchuan (Frontiers in Chemistry, 2021)
Sepiolite was modified with Al3+ via hydrothermal reaction. The substitution amount of Al3+ for Mg2+ and Si4+ located at sepiolite lattice and the influence of substitution amount on the structure, specific surface area, and surface acidity of Al-modified sepiolite were investigated. On this basis, indigo–sepiolite composite pigments were prepared by Al-modified sepiolite and indigo via grinding method to evaluate the influence of Al-modified sepiolite on the structure, bonding strength, and weather resistance of composite pigment. The crystal structure of Al-modified sepiolite had no obvious change after modification. Al3+ mainly substituted Mg2+ located at the octahedron of the sepiolite lattice, and the substitution amount was positively related to the dosage of Al3+. The specific surface area of Al-modified sepiolite decreased and the distribution of channel size became wider after Al modification. In addition, the absolute value of zeta potential decreased as well as the solid acid sites increased with the increase of Al substitution in Al-modified sepiolite. For indigo–sepiolite composite pigments, the structure of Al-modified sepiolite had no obvious change as well. The adsorption amount of indigo in composite pigment after treating by DMSO and Al content as well as weak acid amount in Al-modified sepiolite presented linear correlation, indicating that Al modification could enhance the bonding strength between indigo and Al-modified sepiolite by increasing the amount of coordinated water with Al. For indigo, Al-modified sepiolite could brighten the color and reduce the weather resistance of the prepared composite pigment. The results of this study provide a new idea and basis for regulating the structure and properties of clay and for studying the preparation of composite pigment and clay functional materials.